Structural adsorption mechanism of chloroform in narrow micropores of pitch-based activated carbon fibres. (January 2021) - Yoshikawa, Yasunori; Teshima, Katsuya; Futamura, Ryusuke; Tanaka, Hideki; Iiyama, Taku; Kaneko, Katsumi
Abstract: Activated carbons for the complete removal of CHCl3 from indoor atmosphere and drinking water are in high demand for human health. We must understand the structural adsorption mechanism of CHCl3 on activated carbon to design the optimum pore structures for the removal of even trace amounts of CHCl3 . CHCl3 adsorption on well-characterized pitch-based activated carbon fibres (ACFs) can provide a clear guideline on adsorption sites for CHCl3 and the adsorbed structure of CHCl3 . We measured the N2 adsorption isotherms of ACF with different fractional fillings of preadsorbed CHCl3 ( ϕ, up to 0.8). The difference in pore size distribution of the CHCl3 -preadsorbed ACF indicates preferential CHCl3 adsorption sites in smaller micropores that are not situated in the deepest pore sites. The N2 adsorption of the CHCl3 -preadsorbed ACF provides information on the position of adsorbed CHCl3 relative to pore entrances. CHCl3 molecules form small clusters to adapt to the narrow micropores in the initial stage of adsorption according to the electron radial distribution function analysis of X-ray diffraction. The number of CHCl3 clusters increased and the clusters grew with increasing ϕ . The CHCl3 clusters merge with each other in the final stage of CHCl3 adsorption, giving a liquid-like structure. Graphical abstract: Image 1 Highlights: Chloroform molecules are preferentially adsorbed in smaller micropores. Chloroform molecules form clusters in the micropores during the initial adsorption. Narrow internal micropores are efficient adsorption sites for diluted chloroform.